Analysis of portal vein thrombosis after liver transplantation. Issue 9 (13th May 2019) - Xue, Zhicheng; Zhang, Xuzhi; Li, Zhongqiu; Deng, Ronghai; Wu, Linwei; Ma, Yi
Abstract : Background: Portal vein thrombosis (PVT) is one of the most deadly complications after orthotopic liver transplantation (OLT). This study aimed to identify risk factors and summarize the experience of PVT management after OLT. Methods: The clinical data of 407 adult patients received OLT from July 2011 to December 2015 was retrospectively investigated. Results: The incidence rate of PVT was 2.9% (12/407). Pre‐transplant PVT ( P  = 0.001), post‐operative transfusion of erythrocyte ( P  = 0.006) and platelet ( P  = 0.036) were significantly associated with PVT in the univariate analysis and the appearance of pre‐transplant PVT ( P  = 0.002, odds ratio 6.05) was the independent risk factor according to binary logistic regression. Among patients with PVT, three cases (3/12) received balloon dilation through selective catheterization of portal vein, five (5/12) received balloon‐expandable stent placement, three (3/12) received thrombectomy and surgical revascularization and one (1/12) received retransplantation. Six patients (6/12) died from various complications and the remaining six were followed up with normal liver function and patent portal vein. Conclusions: The risk factors were pre‐transplant PVT and post‐operative transfusion of erythrocyte and platelet. To recipients with high risk, early diagnosis and prompt management of PVT are essential to improve prognosis.